Disability and the good human life - Bickenbach, Jerome Edmund; Felder, Franziska; Schmitz, Barbara, 1968 July 7- (Cambridge disability, law and policy series., 2014)
"This collection of original essays, from both established scholars and newcomers, takes up a recent debate in philosophy, sociology, and disability studies on whether disability is intrinsically a harm that lowers a person's quality of life. While this is a new question in disability scholarship, it also touches on one of the oldest philosophical questions: what is the good human life? Historically, philosophers have not been interested in the topic of disability, and when they are it is usually only in relation to questions such as euthanasia, abortion, or the moral status of disabled people. Consequently disability has been either ignored by moral and political philosophers or simply equated with a bad human life, a life not worth living. This collection takes up the challenge that disability poses to basic questions of political philosophy and bioethics, among others, by focusing on fundamental issues and practical implications of the relationship between disability and the good human life"--Provided by publisher